Confirmed Treponema pallidum pleural effusion in patient with known syphilis - Rachel Shadbolt; Matthew Ing; Michaela Donaghy; Krist Ewe; Y. C. Gary Lee; Edward Fysh (Respirology Case Reports)
Abstract Pulmonary and pleural involvement in Treponema pallidum infection is uncommon. Previously reported syphilis‐related pleural effusions have been described largely based on clinical features combined with positive syphilis serology rather than the detection of T pallidum in pleural fluid or pleural biopsy. We report a case of secondary syphilis and confirmed syphilitic pleural effusion via thoracentesis.